Pengaruh Motivasi Belajar dan Dukungan Sosial Teman Sebaya Terhadap Self Regulated Learning di Sekolah menengah Atas - Putri, Lima Wati Wifit; Darmayanti, Nefi; Hasanuddin, Hasanuddin (Mahesa Research Center, 2023)
This study aims to examine the effect of learning motivation and peer social support on self-regulated learning in high school students. This study uses a quantitative approach with multiple regression analysis techniques. Using 40 students for scale trials and sampling techniques with cluster random sampling obtained as many as 112 students. Data collection techniques used three scales, namely the scale of learning motivation, peer social support, and independent learning. The results are (1) there is a significant positive effect between learning motivation and self-regulated learning where the correlation rx1y = 0.621 with p <0.05, the value of the predictor determinant coefficient (R2) is 0.386 which means learning motivation contributes to influencing oneself. organize learning by 38.6%. (2) There is a significant positive influence between peer social support and self-regulated learning where the correlation rx1y = 0.329 with p <0.05, the value of the predictor determinant coefficient (R2) is 0.257 which means learning motivation contributes to influencing independent learning by 25.7 %. (3) There is a significant influence of learning motivation and peer social support on self-regulated learning, based on the coefficient F reg = 38.550 with p < 0.05, and the correlation coefficient R = 0.644 with p < 0.05 and R2 = 0.414, which means meaning that the contribution of both affects self-regulated learning by 41.4%.